DUKUNGAN ORGANISASIONAL SEBAGAI PEMODERASI PENGARUH ANTARA KECERDASAN EMOSIONAL PADA KEPUASAN KERJA KARYAWAN - Purbo Jadmiko (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
This research has two objectives. First, to examine the effect of emotionalintelligence on employees’ job performance. Second, the moderating of the influenceperceived organizational support on emotional intelligence to job performance. Thesubject of the research is employes who work in hospitals in Yogyakarta. The data iscollected by using questionnaires, distributed to 200 employees. However, 157questionnaires were returned and then analyzed using Moderated Regression Analysis(MRA) to test the hypothesis.The results of this study are emotional intelligence haspositive effect to job satisfaction and perceived organizational support does not moderatethe influence emotional intelligence on job satisfaction.Keywords : emotional intelligence; perceived organizational support; job satisfaction